Closure of postinfarction ventricular septal defect, left ventricular aneurysmectomy, and coronary artery bypass graft: Case report. Issue 5 (September 1973) - Davis, Z.; Borman, J. B.; Freund, U.; Stern, S.
Abstract : Davis, Z., Borman, J. B., Freund, U., and Stern, S. (1973). Thorax, 28, 650-652. Closure of postinfarction ventricular septal defect, left ventricular aneurysmectomy, and coronary artery bypass graft: case report. A 59-year-old patient underwent successful concomitant closure of a ventricular septal defect, left ventricular aneurysmectomy, and coronary artery bypass of the obstructed left anterior descending vessel. The operation was carried out electively three months after the myocardial infarction. Postoperative studies showed normal contractility of the left ventricle and complete closure of the ventricular septal defect. Nine months postoperatively the patient is completely well.